An insight to Malaysian crowdfunding success - Lew, Jian Liang; Cheah, Shi Qing; Cheah, Yi Yee; Chew, Hui Lian; Tang, Siok Man (2019)
In this study, we attempt to determine the factors affecting crowdfunding success in the context of Malaysia, with special look into the variates minimum investment and policy by using secondary data from the reward-based crowdfunding platform, Mystatr. Three types of binary model specifications, which includes Linear Probability Model, Logistic Regression, Probit Regression were employed in this study to ensure robustness of results. We find that project goal, minimum investment, number of backers can predict the success of projects listed on the Malaysian crowdfunding platform, while number of comments and duration does not influence crowdfunding success. This study proposes that policymakers start providing more education to Malaysians about both crowdfunding and reward-based crowdfunding projects in Malaysia, crowdfunding platforms limit the ability of having a choice of crowdfunding policy to the project owner, and start examining the possibilities of regulating reward-based crowdfunding to protect the interests of investors.